Toward a reinterpretation of sacramental theology in the context of pandemics: The case of the Methodist Church in Zimbabwe - M. Mujinga (Acta Theologica)
The advent of Covid-19 and the subsequent closing of religious institutions through lockdowns created a pandemonium that saw churches not being able to meet physically for worship. Covid-19 lockdowns diluted the traditional meaning of sacramental theology for mainline churches. The effects of the pandemic were bad that, churches in Zimbabwe were closed towards lent season in 2020. Mainline churches that used to shun the technologisation of religion were forced to embrace technology in order to be relevant. Unfortunately, sacraments that demanded face to face administration remained a theological dilemma. Using the Methodist Church in Zimbabwe as a case study, the aim of this paper was to challenge the church’s traditional sacramental theology and propose a theological treatise that has relevance in the context of pandemics like Covid-19. The paper proposed a reinterpretation of sacramental theology that makes the rite sacredness to the lives of the parishioners even during pandemics.